2020
DOI: 10.1093/arclin/acaa042
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preliminary Validation of Standardized Regression-Based Change Scores as Measures of Transitional Cognitive Decline

Abstract: Objective An increasing focus in Alzheimer’s disease and aging research is to identify transitional cognitive decline. One means of indexing change over time in serial cognitive evaluations is to calculate standardized regression-based (SRB) change indices. This paper includes the development and preliminary validation of SRB indices for the Uniform Data Set 3.0 Neuropsychological Battery, as well as base rate data to aid in their interpretation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 62 publications
6
13
0
Order By: Relevance
“…However, recall measures require intact consolidation abilities, such that those who are densely amnestic will not be able to give a single scorable answer even when they can participate (Heilman & Valenstein, 2010). That being said, producing extremely low normed scores on individuals tests is relatively common (4.30–22.80%, depending on the task), conforming with a wealth of prior research on the base rates of low scores (Binder, Iverson, & Brooks, 2009; Brooks & Iverson, 2010; Brooks, Iverson, & Holdnack, 2013; Brooks, Iverson, Holdnack, & Feldman, 2008; Brooks, Iverson, & White, 2007; Holdnack et al., 2017; Kiselica, Kaser, et al., 2020; Kiselica Webber et al., 2020a).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, recall measures require intact consolidation abilities, such that those who are densely amnestic will not be able to give a single scorable answer even when they can participate (Heilman & Valenstein, 2010). That being said, producing extremely low normed scores on individuals tests is relatively common (4.30–22.80%, depending on the task), conforming with a wealth of prior research on the base rates of low scores (Binder, Iverson, & Brooks, 2009; Brooks & Iverson, 2010; Brooks, Iverson, & Holdnack, 2013; Brooks, Iverson, Holdnack, & Feldman, 2008; Brooks, Iverson, & White, 2007; Holdnack et al., 2017; Kiselica, Kaser, et al., 2020; Kiselica Webber et al., 2020a).…”
Section: Discussionsupporting
confidence: 80%
“…First, the UDS3NB was designed specifically for clinical research with older adults and is relatively brief (approximately 20–40 minutes in our experience). While there are a growing number of tools to support its application in clinical samples (Devora, Beevers, Kiselica, & Benge, 2020; Kiselica, Kaser, et al., 2020; Kiselica Webber et al., 2020a; Kiselica, Kaser, et al., 2020; Kiselica Webber, & Benge, 2020b; Kiselica, Kaser, et al., 2020; Sachs et al., 2020; Weintraub et al., 2018), it is not as lengthy or extensive as other more commonly utilized batteries that can last several hours (Rabin, Paolillo, & Barr, 2016). Thus, our findings may not generalize to other batteries commonly employed in clinical practice, and they highlight the importance of tailoring testing strategies to the population of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…approach worth noting, including its heavy reliance on process scores from the Auditory Verbal Learning task and its failure to index other cognitive domains, such as visuospatial skills and higher‐level reasoning and problem‐solving abilities. Furthermore, this method uses baseline data, and TCD could alternatively be defined by subtle declines across serial evaluations 9,14 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several promising methods for operationalizing TCD. For example, methods using data from serial assessments revealed that some individuals demonstrate small but statistically significant and clinically meaningful decreases in cognitive performance over time 7–9 . Importantly, those who demonstrate such preclinical cognitive changes are at risk for future mild cognitive impairment or dementia diagnoses.…”
Section: Introductionmentioning
confidence: 99%